Cortical processing of global form, motion and biological motion under low light levels. (April 2016) - Burton, Eliza; Wattam-Bell, John; Rubin, Gary S.; Atkinson, Janette; Braddick, Oliver; Nardini, Marko
Abstract: Advances in potential treatments for rod and cone dystrophies have increased the need to understand the contributions of rods and cones to higher-level cortical vision. We measured form, motion and biological motion coherence thresholds and EEG steady-state visual evoked potentials (SSVEP) responses under light conditions ranging from photopic to scotopic. Low light increased thresholds for all three kinds of stimuli; however, global form thresholds were relatively more impaired than those for global motion or biological motion. SSVEP responses to coherent global form and motion were reduced in low light, and motion responses showed a shift in topography from the midline to more lateral locations. Contrast sensitivity measures confirmed that basic visual processing was also affected by low light. However, comparison with contrast sensitivity function (CSF) reductions achieved by optical blur indicated that these were insufficient to explain the pattern of results, although the temporal properties of the rod system may also play a role. Overall, mid-level processing in extra-striate areas is differentially affected by light level, in ways that cannot be explained in terms of low-level spatiotemporal sensitivity. A topographical shift in scotopic motion SSVEP responses may reflect either changes to inhibitory feedback mechanisms between V1 and extra-striate regions or a reduction of input to the visual cortex. These results provide insight into how higher-level cortical vision is normally organised in absence of cone input, and provide a basis for comparison with patients with cone dystrophies, before and after treatments aiming to restore cone function.